Pilkada Serentak 2018: Transaksi Mahar Politik dan Implikasi Kebijakan Pemilihan Kepala Daerah - Ferza, Ray; Aulia, Nuril Fikri (Research and Development Agency Ministry of Home Affairs, 2020)
According to previous studies, political dowry was practiced in the 2018 simultaneous regional head elections as found in several cases although policies on the prohibition of rewards have been adopted. This is regrettable because political dowry has fairly destructive impacts. For instance, the local governments formed after the elections will have the potential to be corrupt. This study aims to analyze potential political dowry practices in the 2018 regional head elections, their factors, and the policy implication. The research method used in this study is a qualitative approach with a descriptive content analysis on some secondary data. This study found that potential political dowry practices had occurred in the 2018 regional head elections as found in several cases but were difficult to prove by regulations. The factors of a political dowry practice are three elements as involved in any transactional activity, i.e. seller (political party), buyer (prospective regional head candidate), and system (electoral system). The policy implication is to integrate Law No. 7 of 2017 concerning General Elections, Law No. 10 of 2016 concerning Regional Head and Deputy Regional Head Elections, and Law No. 2 of 2011 concerning Political Parties with reinforcement in several aspects, such as the appointment of an independent institution to be permanently responsible for the financial management of political parties, the system with fair, affordable, and accountable opportunities to attain political leadership positions, the rationalization of political finance, the verification of political parties to support participation in simultaneous regional head elections, the reinforcement of information systems in the financial management of political parties, and the reinforcement of the role and independence of the Elections Supervisory Body (Bawaslu) in handling political dowry practices in regional head elections.